Discovery Learning Dalam Peningkatan Pemahaman Mapel Al-Qur’an Hadits Di MTs Miftahul Ulum Jarakkulon - Noor Fatikah; Nurul Indana; Amilatus Syafaah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
The success of a learning process is determined from the factors of students, teachers, facilities and infrastructure, models and learning methods used. The learning model used is able to increase the level of student understanding, one of which is discovery learning. This model is also applied at MTs Distance Kulon. This research method uses qualitative research methods with a descriptive approach. The results of the study stated that the implementation of the Discovery Learning Learning Model were: Planning the Al-Qur'an Hadith learning program, the teacher providing stimulation (stimulus or giving stimulation), the teacher providing problem statements (questions or problem identification) to be solved, the teacher asking students to collect ( data collection) and data processing (data processing), AND the teacher performs verification and assessment of learning outcomes. Students' understanding at MTs Miftahul Ulum Distancekulon on the subject of Al-Qur'an Hadith is proven by fulfilling several indicators of understanding, namely the ability of students to interpret, give examples, clarify, guess or draw conclusions, and re-explain the material they have learned.